Human origins in Southern African palaeo-wetlands? Strong claims from weak evidence. (June 2021) - Schlebusch, Carina M.; Loog, Liisa; Groucutt, Huw S.; King, Turi; Rutherford, Adam; Barbieri, Chiara; Barbujani, Guido; Chikhi, Lounes; Stringer, Chris; Jakobsson, Mattias; Eriksson, Anders; Manica, Andrea; et al.
Abstract: Attempts to identify a 'homeland' for our species from genetic data are widespread in the academic literature. However, even when putting aside the question of whether a 'homeland' is a useful concept, there are a number of inferential pitfalls in attempting to identify the geographic origin of a species from contemporary patterns of genetic variation. These include making strong claims from weakly informative data, treating genetic lineages as representative of populations, assuming a high degree of regional population continuity over hundreds of thousands of years, and using circumstantial observations as corroborating evidence without considering alternative hypotheses on an equal footing, or formally evaluating any hypothesis. In this commentary we review the recent publication that claims to pinpoint the origins of 'modern humans' to a very specific region in Africa (Chan et al., 2019), demonstrate how it fell into these inferential pitfalls, and discuss how this can be avoided.